2021
DOI: 10.1186/s12889-021-11113-z
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adverse birth outcome in Sub-Saharan Africa: analysis of recent demographic and health surveys

Abstract: Background More than 75% of neonatal deaths occurred in the first weeks of life as a result of adverse birth outcomes. Low birth weight, preterm births are associated with a variety of acute and long-term complications. In Sub-Saharan Africa, there is insufficient evidence of adverse birth outcomes. Hence, this study aimed to determine the pooled prevalence and determinants of adverse birth outcomes in Sub-Saharan Africa. Method Data of this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 46 publications
5
32
1
1
Order By: Relevance
“…In the current study, nine hundred and forty-one (28.3%) mothers developed at least one pregnancy complication. This was comparable with findings in Nepal [7], Bangladesh (25%) PLOS ONE [23], and Sub-Saharan Africa [8], in which 27.8%, 25%, and 29.7% of women developed adverse pregnancy outcomes, respectively. A large survey in North Gondar also reported that 28.5% of women developed at least one obstetric complication [15].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study, nine hundred and forty-one (28.3%) mothers developed at least one pregnancy complication. This was comparable with findings in Nepal [7], Bangladesh (25%) PLOS ONE [23], and Sub-Saharan Africa [8], in which 27.8%, 25%, and 29.7% of women developed adverse pregnancy outcomes, respectively. A large survey in North Gondar also reported that 28.5% of women developed at least one obstetric complication [15].…”
Section: Discussionsupporting
confidence: 87%
“…In Nepal, 27.8% of women had adverse obstetric symptoms during the intrapartum period [7]. The prevalence of adverse birth outcomes in Sub-Saharan Africa is 29.7% [8]. Onethird of reproductive-age women in Uganda reported at least one adverse pregnancy outcome [9].…”
Section: Introductionmentioning
confidence: 99%
“…5 A systematic review and metaanalysis study in Sub-Saharan Africa reported a pooled prevalence of 29.7%. 6 Besides, the magnitude of perinatal complication was 18.2% in Butajira, 7 21% in Bale Zone, 8 and 18.3% in Hawassa town. 9 Further, in Southern Ethiopia, one-fourth (24.9%) of multiparous women had at least one adverse birth outcome.…”
Section: Introductionmentioning
confidence: 94%
“…Adverse birth outcomes, including low birth weight, preterm birth and small for gestational age, are the leading causes of infant morbidity and mortality [1]. Worldwide, 75% of neonatal mortality and morbidity is due to adverse birth outcomes [2]. Prenatal depression and anxiety increase the risk of adverse birth outcomes, such as preterm birth, low birth weight and small for gestational age [3].…”
Section: Introductionmentioning
confidence: 99%